The Hotel characteristics and Exclusive features and the ways to employ them for devlement of the Iraqi hotel sector - Samir Khalil Ibrahim Shamto (Iraqi Journal for Administrative Sciences, 2024)
The hotel sector Leads a major role in the development of tourism activity, as well as the development of the service product and its service capabilities that meet the needs and desires of customers. In spite of the great development witnessed by the hotels in the world, and the departure from the function of the accommodation and food and drink, and the trend to the knowledge, entertainment and health, but the Iraqi hotel sector is weak in the trend towards these trends in the global despite the existence of factors of success encouraging and stimulating towards the development of traditional hotel services. This is the problem of the research through which we reached a conclusion; The failure of the guest to achieve a hotel trip beyond his mental perceptions, and the decline of hotel services in Iraq on accommodation services, food and drink services, and other traditional services, and the absence of modern technology in hotel reservations that are made online in Iraqi hotels.